Improved governance: Creating supportive environments for diet and nutrition policies - Resnick, Danielle; Nogales, Maria-Teresa (International Food Policy Research Institute, 2024)
Most policy interventions to improve diet quality and nutrition require sound governance to be successful. Governance encompasses the interrelationships between formal institutions and informal modes of power, across different geographic scales, and among state and non-state actors. This chapter examines how multilevel and multistakeholder governance can be strengthened to improve diets, with a focus on enhancing state capacities, navigating corporate influence, and fostering citizen agency. The chapter highlights existing challenges in each of these areas while also discussing approaches that have potential to improve the governance environment at national and local scales.